2019
DOI: 10.5897/ajmr2019.9147
|View full text |Cite
|
Sign up to set email alerts
|

Detection of multidrug-resistant enterobacteria simultaneously producing extended-spectrum -lactamases of the PER and GES types isolated at Saint Camille Hospital Center, Ouagadougou, Burkina Faso

Abstract: Resistance to a wide variety of common antibiotics is observed among clinical strains designated as extended-spectrum β-lactamase (ESBL) producers. These produce enzymatic proteins that effectively inactivate cephalosporins and aztreonam and are a serious global health problem that complicates treatment strategies. Many studies report a high prevalence of ESBL producers among Gram-negative bacilli. The purpose of this work was to identify resistance genes in enterobacterial strains. Gramnegative bacilli resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…In the present study we detected the bla NDM, bla SHV and bla TOHO genes in clinical strains of Gramnegative bacilli isolated from urocultures or stool cultures at CERBA, Ouagadougou, Burkina Faso. Most of the resistant strains 78.38% (29/37) in the present study were isolated from urine like previous studies by our research team in Burkina Faso [19,20] and Togo [22,24]. The uropathogenic species were mainly E. coli (59.46%) and Klebsiella sp (32.43%).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…In the present study we detected the bla NDM, bla SHV and bla TOHO genes in clinical strains of Gramnegative bacilli isolated from urocultures or stool cultures at CERBA, Ouagadougou, Burkina Faso. Most of the resistant strains 78.38% (29/37) in the present study were isolated from urine like previous studies by our research team in Burkina Faso [19,20] and Togo [22,24]. The uropathogenic species were mainly E. coli (59.46%) and Klebsiella sp (32.43%).…”
Section: Discussionsupporting
confidence: 66%
“…Third generation cephalosporin (C3G) resistance rates of 45.9%, 43.24% and 37.84% were recorded for Cefotaxime, Ceftazidime, Ceftriaxone, respectively, in the present study. High resistance to C3G has also been reported in previous studies in Burkina Faso [19][20][21], Togo [23,24,32] and Nigeria [33]. Drug pressure in hospitals, poor compliance with treatments as well as the abusive use of antibiotics sometimes without medical prescriptions constitute the main factors in the emergence and spread of multiresistant pathogens [33].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In Africa, IMP enzymes had been in Egypt (Masoud et al, 2021;Benmahmod et al, 2019;Abbas et al, 2019), Morocco (Barguigua et al, 2013), Tunisia (Chouchani et al, 2011;Dziri et al, 2020), Tanzania (Mushi et al, 2014) and Sudan (Adam and Elhag, 2018). In Burkina Faso, most of the studies were much focused on ESBLproducing Enterobacteriaceae which occurs resistant to beta-lactam (Metuor Dabire et al, 2013;Metuor et al, 2019a;Metuor Dabire et al, 2019b;Tiemtore et al, 2022) at the expense of carbapenemases, mainly MBL despite the threat they represent for heath care. Nevertheless, previous studies (Sanou et al, 2020;Dembele et al, 2021;Kabore et al, 2022Kabore et al, , 2023 have reported resistance to carbapenems in GNB by the production of carbapenemases.…”
Section: Introductionmentioning
confidence: 99%